2002
DOI: 10.4049/jimmunol.168.8.3697
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Biasing Immune Responses by Directing Antigen to Macrophage Fcγ Receptors

Abstract: An immune response can deviate toward either a Th1- or Th2-like response. In this work we examine the contribution that activated macrophages and IgG Abs make toward this deviation. The use of activated macrophages as APCs resulted in a strong polarized T cell response that was predominated by IFN-γ. However, when Ag was targeted to FcγRs on these macrophages, the T cell response was reversed and biased toward a Th2-like response. This Th2-like phenotype was stable and was retained when the T cells were subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 23 publications
(24 reference statements)
9
169
0
Order By: Relevance
“…Fc␥R engagement induces IL-12 production, and has also been shown to effectively prime CTL responses in vivo (30), suggesting that DC activation by ICs would result in Th1 polarization. In contrast, macrophages were recently reported to reverse a Th1-like response toward a Th2-like phenotype when Ag was targeted on Fc␥R (31). The signaling pathways activated during DC maturation leading to the secretion of different cytokines are still unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Fc␥R engagement induces IL-12 production, and has also been shown to effectively prime CTL responses in vivo (30), suggesting that DC activation by ICs would result in Th1 polarization. In contrast, macrophages were recently reported to reverse a Th1-like response toward a Th2-like phenotype when Ag was targeted on Fc␥R (31). The signaling pathways activated during DC maturation leading to the secretion of different cytokines are still unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, complement involvement in plaque clearance may be more pronounced at higher doses of antibody, where there would be an increased density of antibody bound to plaques. Interestingly, in contrast to other macrophage-activation paradigms, it has been shown that activation of phagocytic cells through Fc receptors results in production of the antiinflammatory cytokine IL-10 and inhibition of proinflammatory IL-12 (22). Thus, antibodies against A␤ may allow resolution of an otherwise chronic, unresolving inflammatory response associated with plaques in AD by both clearing A␤ and altering the inflammatory environment.…”
Section: Resultsmentioning
confidence: 99%
“…Distinction between immunosuppressive alternatively activated macrophages, activated by IL-4 or glucocorticoids, and anti-inflammatory type 2 macrophages, which promote Th2 cell responses [57] and are elicited by TLR or Fcc receptor ligation [58], has been suggested. Verreck and coworkers recently described that human macrophages, polarized by M-CSF rather than GM-CSF (Mf-2), subvert T cell responses to mycobacteria by down-regulating antigen-presenting activities and producing IL-10 rather than IL-12 or IL-23 [59].…”
Section: Discussionmentioning
confidence: 99%